Prediction of instantaneous likeability of advertisements using deep learning. Issue 3 (21st May 2021) - Saha, Dipayan; Rahman, S.M.Mahbubur; Islam, Mohammad Tariqul; Ahmad, M. Omair; Swamy, M.N.S.
Abstract: The degree to which advertisements are successful is of prime concern for vendors in highly competitive global markets. Given the astounding growth of multimedia content on the internet, online marketing has become another form of advertising. Researchers consider advertisement likeability a major predictor of effective market penetration. An algorithm is presented to predict how much an advertisement clip will be liked with the aid of an end‐to‐end audiovisual feature extraction process using cognitive computing technology. Specifically, the usefulness of different spatial and time‐domain deep‐learning architectures such as convolutional neural and long short‐term memory networks is investigated to predict the frame‐by‐frame instantaneous and root mean square likeability of advertisement clips. A data set named the 'BUET Advertisement Likeness Data Set', containing annotations of frame‐wise likeability scores for various categories of advertisements, is also introduced. Experiments with the developed database show that the proposed algorithm performs better than existing methods in terms of commonly used performance indices at the expense of slightly increased computational complexity.